Trade-offs analysis in predictive current control of multi-phase induction machines. (December 2018) - Arahal, Manuel R.; Barrero, Federico; Durán, Mario J.; Ortega, Manuel G.; Martín, Cristina
Abstract: In this paper, an assessment tool for stator-current predictive control of multi-phase induction machines is presented. The tool stems from a parameter analysis of the class of predictive controllers. This analysis exposes the underlying trade-offs among variables of interest. A reduced set of performance criteria is proposed for the parameter analysis. It is shown how the locus of the performance measures can be used to compare different types of predictive controllers. As application examples, some of the most common predictive strategies are reviewed. It is shown that the proposed assessment tool allows ranking the types of controllers under comparison. Additionally, the proposed tool can be used in control design and parameter tuning. The simulation results are backed by real experimentation using a six-phase motor.